Impact Analysis of The Benefits of Heach Heater (Eichornia Crassipess) for The Environment in The Batu Jai Dam Area, Central Lombok District - Muhsin; Khairil Anwar; Yudi Hermawan (Postgraduate, University of Mataram, 2023)
The Batu Jai Dam functions as an irrigation facility in the agricultural areas of Penujak, Setanggor, Darek, Ungga, Ranggagata, and around Praya Barat District, Central Lombok Regency with an area of â€‹â€‹3,350 ha. Water hyacinth is a dangerous weed because it grows very fast, so a model for the control and utilization of water hyacinth (Eichornia crassipes) must be carried out. One way to do this is to utilize the water hyacinth plant into a marketable product such as fertilizer, handicraft products and others. The technique of determining the location and population is done by purposive sampling method. The results of a search with a questionnaire on 50 respondents about the benefits of water hyacinth plants obtained the benefits of water hyacinth plants according to the people around the Batujai dam, namely 40% stated that the benefits of water hyacinth plants as raw materials for making fertilizer, 30% as raw materials for crafts such as sandals, bags, and other, 20% of water hyacinth plants are used as medicine and only 5% of the people consider water hyacinth plants as weeds. Whereas in extension activities with 35 participants, 48.6% stated that water hyacinth plants could be useful as raw materials for crafts, 37.1% stated that they were used as fertilizer raw materials, 3% stated that they were useful as medicine and 2% stated that they are weeds. concluded that water hyacinth plants are economically, socially, ecologically beneficial. This shows that water hyacinth plants are beneficial to the environment around the dam. Based on the results of the FGD, there were 3 important activities carried out by related agencies based on the results of counseling and interviews with the community, namely water hyacinth plants as fertilizer, as raw materials for crafts and determining the location of water hyacinth cultivation outside the Batujai Dunngan. Â